AN EXAMINATION OF THE POTENTIAL IMPACT OF RISK ON VIABILITY ASSESSMENTS FORFINANCIALLY DISTRESSED FIRMS: THE CASE OF PROFESSIONAL USER GROUPS OF COMPANY ACCOUNTS - Sylvia Constantinides (Asian Academy of Management Journal, 2007)
Risky conditions in conjunction with individuals' attitude to risk would normally lead to risk-averse behavior (Fishbein & Ajzen, 1975; Ajzen & Fishbein, 1980). In this research, risk-averse behavior (the dependent variable) relates to the "going-concern" opinion of financially distressed firms. A logistic regression model used as predictors of risk measurements (risky conditions and risk attitude) correctly predicts 97.6% of the nongoing concern opinions. In conclusion, the empirical evidence demonstrates a subtle impact of risk on individuals' behavior despite the fact that distinct statistical tests do not fully support this.